The one vice Coronavirus should wipe out - Hasan, Md. Mahmudul (2020)
Governments of Muslim-majority countries in general and masjid authorities in particular have added reasons to ban smoking. First, it is one of worst forms of wasting money, and wastage is haram in Islam. Secondly, smoking leads to many incurable diseases and can be regarded as slow suicide, and suicide is one of the cardinal sins in Islam. Thirdly, according to Islam, our health is a trust from God. Humans have no right to harm their health. Fourthly, smoking is harmful to neighbor, and causing harms to neighbors is forbidden in Islam.